2006
DOI: 10.1111/j.2006.0030-1299.14446.x
|View full text |Cite
|
Sign up to set email alerts
|

On the virtue of being the first born: the influence of date of birth on fitness in the mosquitofish, Gambusia affinis

Abstract: We found in an earlier study that mosquitofish (Gambusia affinis and G. holbrooki) ceased reproduction in the late summer, long before the end of warm weather, stored fat, then utilized reserves to survive the winter and initiate reproduction the following spring. We hypothesized that this pattern of fat utilization was a life history adaptation that enabled the fish to acquire food resources in the autumn then allocate them to reproduction the following spring when the fitness of the young would be greater. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…This was earlier and faster in females, leading to higher average condition values than males. From July onwards, because of extreme reproductive effort (Reznick et al 2006), most 1+ individuals died after reproduction and the rest were only able to maintain their condition until winter. Alcaraz & García-Berthou (2007) observed that the somatic condition of Gambusia holbrooki females was lower in populations in high salinity conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This was earlier and faster in females, leading to higher average condition values than males. From July onwards, because of extreme reproductive effort (Reznick et al 2006), most 1+ individuals died after reproduction and the rest were only able to maintain their condition until winter. Alcaraz & García-Berthou (2007) observed that the somatic condition of Gambusia holbrooki females was lower in populations in high salinity conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A general benefit of capital breeding is that feeding is decoupled from breeding, with the possibility of breeding when the offspring have the highest value. In many seasonal environments peak offspring fitness is early in the feeding season (Nilsson 1999, Reznick et al 2006, favouring capital breeding. This is also predicted for the copepod studied here (P3, P4) where the ideal egg should be laid even prior to the feeding season.…”
Section: ______mentioning
confidence: 99%
“…To date, few studies have examined shifts in reproductive timing in response to predator-induced mortality, although a number of examples are known for the effects of abiotic sources of mortality (e.g. desiccation, reduced energy sources due to winter; Thomson 1950;Lack 1954;Newman 1988;Brinkhof et al 1993;Van Noordwijk et al 1995;Reznick et al 2006b). Reproductive timing can also influence individual viability by minimizing negative effects of offspring production (e.g.…”
Section: Reproductive Strategies: Transcending Predators Through Lifementioning
confidence: 99%